A path model analysis of preform students’ factors and comprehension strategies on cognitive learning outcomes associated with text comprehension - Hunsu, Nathaniel J.; Adesope, Olusola Olalekan; Yli-Piipari, Sami R. (Frontiers in Education, 2024)
Introduction The ability to understand text is influenced by various factors, including the learner’s cognitive abilities and previous experiences. This study examined the correlation between two pre-existing learner characteristics, three comprehension strategies used while reading, and two cognitive outcomes related to text comprehension. Methods The study involved 109 undergraduate Biology students, who were instructed to perform think-aloud exercises while reading biology texts and complete post-reading tests. The participants typed out their thoughts about the text when prompted. Their verbal protocols were coded and analyzed. Results Statistically significant correlations were only observed between prior knowledge, presage skill, recall, and comprehension. The direct relationships between prior knowledge and cognitive strategies were not significant, and the relationship between participants’ presage skills and the comprehension strategies they employed while reading was not significant. Discussion The study revealed that prior knowledge had a more significant impact on cognitive learning outcomes than the students’ prior cognitive skills and the comprehension strategies they employed while reading. Additionally, the participant’s performance on the learning outcomes was influenced by at least one of the comprehension strategies and their prior knowledge.